PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN HASIL BELAJAR SISWA - Tabliana, (UNISAN JURNAL, 2024)
This exploration examines the utilization of data innovation as a learning asset to further develop understudy learning results in Islamic strict training subjects at SD Negeri 19 Tanah Abang. The focal point of this examination is on issues connecting with how to involve data innovation as a learning asset to further develop understudy learning results in Islamic strict training subjects at SD Negeri 19 Tanah Abang. The information assortment strategies utilized were meetings, perception and documentation in regards to the SD Negeri 19 Tanah Abang organization in using data innovation as a learning asset to further develop understudy learning results in Islamic strict training subjects at SD Negeri 19 Tanah Abang. Information was acquired through perception, direct meetings, and documentation, Islamic strict subject educators and understudies. Educators have used data innovation as a learning asset, specifically advancing by utilizing data innovation accessible at school as a learning instrument, like workstations, web, LCD. what's more, projector. The examination results show that. To begin with, the utilization of data innovation in Islamic strict subjects, educators use picking up utilizing existing mechanical hardware, for example, PCs, LCDs, power focuses and the web. Through data innovation, understudies effectively acknowledge the material introduced by the educator and understudy learning exercises in class are more dynamic, the homeroom air is helpful so that learning is more successful and productive and doesn't look dull. The subsequent instructor can use data innovation since he needs to cultivate understudies' happiness regarding Islamic strict subjects. It has been demonstrated that understudies who get material by seeing and hearing will continuously recollect, comprehend and be aware. Consequently, there is an exceptional interest among understudies in concentrating on Islamic strict training so they can without much of a stretch retain the material due to the high energy for understudy learning. These discoveries can add to educators in picking the right learning assets as per learning targets, topic, understudy conditions, accessible offices and framework and instructor capacities, to make viable figuring out how to accomplish the normal objectives